Analisis Pengaruh Pelatihan, Pengembangan Karir Dan Kompetensi Terhadap Kinerja Karyawan BPKAD Blitar - Dewi Anggraini (Universitas Islam Kadiri, 2020)
This study aimed to determine impact of training, career development and competence both simultaneously and partially on employee performance at the Regional Financial and Asset Management Agency of Blitar District. This type of research is explanatory research, multiple linear regression data analysis techniques. The results of the study is a positive and significant partial impact of training on employee performance, Impact of career development on employee performance, Impact of competence on employee performance. And also Impact of training, career development and competency simultaneously on employee performance in the Regional Financial and Asset Management Agency of Blitar District.